Sintesis Bahan M-Hexaferrites dengan Doping Logam Co Menggunakan FTIR - Susilawati Susilawati; Khairunnisa Khairunnisa; Aris Doyan (Department of Physics Education, Universitas Mataram, 2015)
Has successfully carried out the study synthesis of materials M-heksaferit with doping metal Co using FTIR. The study was conducted to see the phase that forms on M-hexaferrites material by adding a transition metal element cobalt (Co) with the mole fraction x 0, 0.2, 0.5, 0.8, 1.0 done drying with T 80ÃÂ°C for 2 hours and calcined the T 400, 600, 800ÃÂ°C for 4 hours. Barium M-hexaferrites BaFe12O19 characterized using Fourier transform infrared spectroscopy (FTIR), the picture looks FTIR results for the mole fraction x 0.2, 0.5, 0.8 and 1.0 located on T 8000C.